2006
DOI: 10.3164/jcbn.39.46
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Diversity of Patients with Reflux Esophagitis: Effect of Omeprazole Treatment

Abstract: Summary Objective: A number of clinical trials have reported that proton-pump inhibitors are efficacious in the treatment of upper abdominal symptoms, but most of these trials have been carried out in Caucasians. This study investigated the type of upper abdominal symptoms reported by Japanese patients with reflux esophagitis and the efficacy of omeprazole for treating their symptoms.Methods: A total of 234 patients aged ≥20 years with grade A to D reflux esophagitis were enrolled in this multicenter, open stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…Numbers in parenthesis indicate the % of improved patients were unable to clearly demonstrate the efficacy of rebamipide for control of reflux symptoms in NERD patients who were refractory to PPI therapy. Several investigators have demonstrated that patients with GERD have not only reflux symptoms but also several dyspeptic symptoms, and the dyspeptic symptoms in GERD patients are often improved by PPI administration [33][34][35]. The present results showed that dyspeptic symptoms in patients who had received rebamipide were more frequently improved.…”
Section: Discussionsupporting
confidence: 48%
“…Numbers in parenthesis indicate the % of improved patients were unable to clearly demonstrate the efficacy of rebamipide for control of reflux symptoms in NERD patients who were refractory to PPI therapy. Several investigators have demonstrated that patients with GERD have not only reflux symptoms but also several dyspeptic symptoms, and the dyspeptic symptoms in GERD patients are often improved by PPI administration [33][34][35]. The present results showed that dyspeptic symptoms in patients who had received rebamipide were more frequently improved.…”
Section: Discussionsupporting
confidence: 48%
“…We also achieved similar results for both questionnaires in this direct comparative study, with no differences between the two in regard to sensitivity or specificity. A possible reason for the relatively low specificities for GERD of the two investigated questionnaires in this study might be the difficulty in distinguishing between acid‐reflux‐related symptoms and dyspeptic (dysmotility) symptoms in patients with GERD in Japan, because of the multidimensionality of GERD symptoms and the high proportion of mild disease in Japanese patients 3,27,28 …”
Section: Discussionmentioning
confidence: 89%
“…On the contrary, in Japan it is not known which drug is the first choice in controlling overall symptoms [10]. Adachi et al [11] recently reported symptom diversity in GERD patients, i.e., overlap of subtype symptoms and omeprazole efficacy independent of subtype. We therefore planned a study to investigate the efficacy of PPI compared to treatment with H 2 receptor antagonists for treatment of upper abdominal symptoms in patients with reflux esophagitis.…”
Section: Introductionmentioning
confidence: 97%